Expression of serum miR‐135a in patients with allergic rhinitis and its relationship with Treg/Th17 balance - Jing Cai; Fang Wang; Sheng‐Liu Shi (Kaohsiung Journal of Medical Sciences)
Abstract The dysregulation of microRNA (miRNA) expression contributes to the development of allergic rhinitis (AR). This study investigates serum miR‐135a levels and their association with regulatory T cell (Treg) and T helper cell 17 (Th17) balance in AR patients. A total of 93 AR patients and 76 healthy controls were retrospectively recruited. Levels of serum miR‐135a, peripheral blood Th17 and Treg cells, and Treg/Th17‐related cytokines were measured. We assessed the diagnostic value of serum miR‐135a for AR and its relationship with Treg/Th17 balance. AR patients showed significantly elevated immunoglobulin E (IgE), peripheral blood Th17 cells, and IL‐17 and IL‐6 levels, alongside reduced serum miR‐135a, Treg cells, IL‐10, TGF‐β1, and Treg/Th17 ratios. A serum miR‐135a of ≤0.536 demonstrated diagnostic potential for AR. Patients with higher serum miR‐135a levels displayed increased Treg cell level and Treg/Th17 ratios, reduced Th17 cell, and lower total nasal symptom score (TNSS). Serum miR‐135a levels in AR patients negatively correlated with TNSS, IL‐17, IL‐6, and Th17 cell percentages, and positively correlated with IL‐10, TGF‐β1, Treg cell percentages, and Treg/Th17 ratios. Collectively, decreased serum miR‐135a levels in AR patients are associated with Treg/Th17 balance, supporting miR‐135a as a potential biomarker for AR diagnosis.